Exploring the bilateral and hybrid model in deregulated electricity market - Mohd Yassin, Zaris Izzati (2014)
This thesis is reviewing all the outcomes towards the entire work that has been done for this Master‟s Project which is entitled „Exploring the Bilateral and Hybrid Model for Deregulated market‟. The outcome is about the background of the restructuring of Electricity Supply Industry (ESI) especially for Malaysia Electricity Supply Industry (MESI). Before the restructuring of the MESI, Tenaga Nasional Berhad, (TNB) was monopolized electricity market from generation, transmission, and distribution sector. It comes to the end when Independent Power Producer, (IPP) introduced by the Malaysian Government with the aim to avoid shortage and facilitate competitions among generators and the first IPP in Malaysia is YTL Corporation Sdn. Bhd. In 2001, the first of restructuring model was introduced is the Single Buyer Model and TNB is expected to be the single buyer in this model. From the literature review which has displayed the weakness of this model, this Master Project thus has proposed two other models in deregulated electricity market that can be applied for MESI which are the Bilateral Market Model and Hybrid Market Model in order to carry on the MESI previous plan towards restructuring. In this project, the proposed models are designed to carry out the power generation revenue for selected Independent Power Producers (IPPs) in Malaysia in order to accommodate a fair competitive trading between power producers and produce win-win situation to all involved market participants. The analysis from the results obtained in the proposed model illustrates guaranteed incomes for all selected IPPs, the pattern of the profits for each IPP and the factors that determines those incomes and profits. The obtained results also bring out the advantages and disadvantages from these market models to all involved parties including IPP, utility company which is TNB, government and the end users.